2014
DOI: 10.1159/000363386
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Pattern of Hepatitis C Virus Genotypes and Correlation with Viral Load and Risk Factors in Chronic Positive Patients

Abstract: Objective: Hepatitis C virus (HCV) has emerged as a leading cause of chronic hepatitis, liver cirrhosis and hepatocellular carcinoma worldwide. The purpose of this study was to describe the distribution pattern of HCV genotypes in chronic hepatitis patients in the Campania region of southern Italy and estimate their association with risk factors and viral load. Materials and Methods: 404 consecutive HCV ribonucleic acid-positive patients were included in the study. HCV genotyping was carried out by the HCV lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 46 publications
6
16
2
Order By: Relevance
“…Our data also seem to confirm the existence of 2 transmission patterns of the HCV genotypes in Italy, as already reported by other authors [21,26,28] . The first is characterized by infections with subtypes 1b and 2a/2c, mainly in adults aged over 60 years, consistent with healthcarerelated practices in the past.…”
Section: Discussionsupporting
confidence: 92%
“…Our data also seem to confirm the existence of 2 transmission patterns of the HCV genotypes in Italy, as already reported by other authors [21,26,28] . The first is characterized by infections with subtypes 1b and 2a/2c, mainly in adults aged over 60 years, consistent with healthcarerelated practices in the past.…”
Section: Discussionsupporting
confidence: 92%
“…Although our study is simply a retrospective analysis and prevents us to make any hypothesis about mechanisms of HCC progression, our data clearly shows that a significantly higher percentage of HCC patients (83.7%) shows HCV-RNA in their sera compared to the control group (61.4%) (p < 0.001), suggesting that HCC patients have a risk of HCV active infection almost 1 and half times higher than patients without HCC, even if we did not find any correlation between high levels of viremia and advanced liver stage, as reported by other authors [38,67]. The role of genotypes 1b and 3 in increasing the risk of HCC development has been widely questioned recently and even though numerous studies have often suggested their association with the HCC carcinogenetic progression [68][69][70][71][72][73][74], especially in patients with underlying cirrhosis, [38][39][40][41][75][76][77], probably for the strict correlation existing between these subtypes and liver damage, no consensus has emerged yet.…”
Section: Resultssupporting
confidence: 74%
“…Although in our area, as we previously reported [37,38], genotype 1b is the most common subtype, our data show that its prevalence in HCC patients is significantly higher (67.9%) if compared to the control group (54.4%) (p < 0.001), suggesting that HCC patients have a risk to be infected by subtype 1b quite 2 times greater than patients without HCC. Although a minority of treated control group patients achieved SVR, in order to minimize the potential confounding effect of SVR, we adjusted the estimates for SVR achievement, and we also provided a separate multivariate analysis that excluded all patients who had achieved SVR.…”
Section: Resultscontrasting
confidence: 52%
See 2 more Smart Citations